Characterising the role of microglia in the early stages of brain metastasis - Andreou, K (2016)
Brain metastasis is a common complication of breast cancer patients with poor survival. Histological analysis of autopsy samples from patients with brain metastases suggests that microglia, rather than lymphocytes, are the major immune population activated around the metastatic foci. Microglia and macrophages are versatile immune cells with the ability to polarise to different functional phenotypes depending on the microenvironment they reside in. Clinical and preclinical data report both tumourigenic and cytotoxic effects of microglia and macrophages in the tumour microenvironment. However the role and phenotype of microglia during the early stages of metastatic growth in the brain has not yet been fully determined. The aim of this thesis, therefore, was to determine the temporal and spatial profile of microglial activation in a mouse model of brain metastasis, and to assess the effect of M2 (anti-inflammatory) microglial depletion on tumour growth. Iba1, a specific marker for microglia, was robustly expressed around 4T1 metastatic foci. Quantitatively, microglial activation positively correlated with tumour volume over a 28 day study. Moreover, populations of classically (M1) and alternatively (M2) activated microglia were identified by co-localisation of Iba1 with inducible nitric oxide synthase (iNOS) and cyclooxygenase 2 (COX2), or mannose receptor 1 (MRC1) and arginase 1 (Arg1), respectively. M1 and M2 microglia were found within the tumour microenvironment as well as adjacent to the 4T1 foci. Temporally, MRC1+ M2 microglia maintained their levels across the time-course, as did iNOS+ M1 cells. In vivo depletion of MRC1+ microglia using mannosylated clodronate liposomes at an early stage significantly reduced intracranial tumour burden in the metastatic brain. Moreover, increased levels of apoptosis, indicated by cleaved caspase 3 expression, were associated with 4T1 tumour foci in the animals injected with clodronate liposomes compared to those injected with control liposomes. A genetic mouse model of deficient M2 polarisation of myeloid cells was also employed as an alternative approach to further validate the aforementioned findings. However, there was no significant decrease in intracranial metastasis burden in the specific model, possibly due to inefficient microglial targeting. Our findings suggest that microglia are effectors of the inflammatory response in the early stages of brain metastasis. We have shown that M1 and M2 phenotypes co-exist within the tumour microenvironment and that targeting the anti-inflammatory M2 microglial population could be of therapeutic benefit. Further research will provide insights into the M2 molecular signatures that sustain metastatic outgrowth in the brain with the aim of therapeutic intervention.